Performance Assessment of a Temperature‑Based Model in Estimating GSR Across Different Latitudes of Cameroon - Mboumboue, Edouard; Moungnutou Mfetoum, Inoussah; Arim, Ahmed Ismail; Njomo, Donatien (New Energy Exploitation and Application, 2025)
Among all climatic parameters, solar radiation is one, if not the most, involved in different applications (meteorology, agriculture, environment, etc.). However, due to economic constraints (especially in low‑income countries like ours), it is not always measured. Over the years, several empirical correlations estimating global solar radiation (GSR) have been developed around the world by different authors. The objective of this study is to evaluate the performance and accuracy of a temperature‑based model and to estimate the GSR received at four localities (Nanga Eboko, Ngaoundere, Tchollire and Maroua) in Cameroon. The studied model is that proposed by Hargreaves‑Samani in 1982. It takes into account the latitude of the site and the daily minimum and maximum air temperatures. With commonly used statistical indicators (whose values are all within the acceptable range), the measured and estimated GSR values were compared and analyzed. According to the results, this model gives for the study area, a reasonable degree of good fitting and correlation between measurements and estimations. We also found that the further we move towards the north, the higher solar radiation is received and the performance of the model improves. Thus, from south to north, the country receives in average values, 4.6437 kWh m−2 d−1 at Nanga Eboko, 5.5667 kWh m−2 d−1 at Ngaoundere, 5.6968 kWh m−2 d−1 at Tchollire and 5.7936 kWh m−2 d−1 at Maroua. In case of missing data and taking into account the foregoing, we can consider the studied model as an accurate and useful tool in predicting GSR in the study area and similar geographical locations around the world.